OPTIMIZING THE RM WORKBENCH TO EMPOWER RELATIONSHIP MANAGERS AND SUPPORT WHOLESALE BUSINESS PORTFOLIO GROWTH AT BBRI - Nugraini Rahmaniasari; Utomo Sarjono Putro (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study focuses on enhancing the RM Workbench at BBRI to support Relationship Managers (RMs) in driving wholesale business portfolio growth amidst challenges in the MSME segment. The research identifies a significant gap between the Workbench's intended functionalities and actual adoption due to usability issues and feature limitations. Leveraging frameworks such as the Technology Acceptance Model (TAM), Fishbone Diagram, SWOT/TOWS analysis, and CRM principles, the study systematically evaluates the factors affecting adoption. The findings reveal critical barriers, including the lack of intuitive design, insufficient training, and integration challenges. Strategic recommendations include adding advanced analytics, streamlining workflows, and incorporating predictive modeling to align the Workbench with RMs' needs. The proposed visual mockup aims to enhance usability and adoption, ensuring the RM Workbench becomes a central tool for improving operational efficiency, strategic decision-making, and client relationship management. This initiative supports BBRI's goal to diversify beyond MSME and strengthen its wholesale business segment to sustain long-term profitability and market leadership